The tumor-suppressor gene LZTS1 suppresses colorectal cancer proliferation through inhibition of the AKT–mTOR signaling pathway. Issue 1 (28th April 2015) - Zhou, Wei; He, Mei-Rong; Jiao, Hong-Li; He, Liu-Qing; Deng, Dan-Ling; Cai, Juan-Juan; Xiao, Zhi-Yuan; Ye, Ya-Ping; Ding, Yan-Qing; Liao, Wen-Ting; Liu, Si-De
Highlights Decreased expression of LZTS1 was correlated to aggressive characteristics and poor survival of patients with colorectal cancer. LZTS1 inhibits colorectal cancer cell proliferation and tumor growth. LZTS1 inhibited cell proliferation and tumor growth in colorectal cancer partially via suppression of AKT–mTOR signaling.